Le labyrinthe des ayants droit - Jean Jonassaint (Continents manuscrits)
In the wake of an analysis of the difficulties encountered or envisioned to consult, reproduce, distribute or broadcast (fully or partially) written or audio-visual documents by Aimé Césaire, Saint-John Perse, Frankétienne and Boisrond-Tonnerre, which are archived or not, this article calls for a simplification and an harmonization of the rules to access to archives, and the establishment of a standard set of procedures to deal with copyright holders that be efficient and fair for all parties.